Fatigue crack propagation along interfaces of selective laser melting steel hybrid parts. Issue 11 (11th June 2019) - Santos, Luis M.S.; Ferreira, José A.M.; Borrego, Luis P.; Costa, Jose D.; Capela, Carlos; de Jesus, Joel
Abstract: Selective laser melting (SLM) is an emerging additive manufacturing technology, capable of producing complex geometry components. The current work studied both the effect of substrate material and mean stress on the fatigue crack growth behaviour along interfaces of bi‐material specimens, substrate, and part by SLM. Fatigue tests were carried out in agreement with ASTM E647 standard, using 6‐mm‐thick compact specimens. The substrate steel has only a negligible effect both on the fatigue crack propagation rate and on the crack path. The failure occurs in the material additively manufactured by SLM, near the interface. The mean stress produced only a reduced influence on the fatigue crack propagation rate in the Paris regime. For larger values of Δ K, where K max approaches K Ic, a significant influence of the mean stress was observed. In spite of nondetection of crack closure, the application of overloads promoted significant fatigue crack retardation, quite similar for both substrate materials, probably due to the crack bifurcation during the overload.